Effectiveness of the ECB programme of asset purchases: Where do we stand? - Kerstin Bernoth; Michael Hachula; Michele Piffer; Malte Rieth (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The ECB has engaged in several forms of unconventional monetary policy since 2007. This report documents empirically that the implemented measures were effective. In a counter-factual analysis, the report simulates the effects of an unconventional monetary policy shock of -10 basis points to euro area sovereign yields, consistent with the effect of the first an-nouncement of the Expanded Asset Purchase Programme (EAPP). The simulation shows that the surprise expansion led to significant increases of output, prices, and inflation expecta-tions, as well as to a drop in the unemployment rate. The shock is transmitted to the eco-nomy through lower public and private interest rates, and an increase in bank credit to the private sector. The results also suggest that the effects of unconventional monetary policy interventions do not differ much from those of conventional policy measures.
Keywords: 330